2017
DOI: 10.1016/j.imavis.2016.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Current research in eye movement biometrics: An analysis based on BioEye 2015 competition

Abstract: On the onset of the second decade of research in eye movement biometrics, the already demonstrated results strongly support the promising perspectives of the field. This paper presents a description of the research conducted in eye movement biometrics based on an extended analysis of the characteristics and results of the "BioEye 2015: Competition on Biometrics via Eye Movements". This extended presentation can contribute to the understanding of the current level of research in eye movement biometrics, coverin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 63 publications
0
5
0
1
Order By: Relevance
“…However, even the earliest studies of fixation behaviour noted considerable individual differences 19,20 , and basic occulomotor traits vary reliably between observers [21][22][23][24][25][26] . Recent twinstudies revealed that social attention and gaze traces across complex scenes are highly heritable 27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…However, even the earliest studies of fixation behaviour noted considerable individual differences 19,20 , and basic occulomotor traits vary reliably between observers [21][22][23][24][25][26] . Recent twinstudies revealed that social attention and gaze traces across complex scenes are highly heritable 27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…However, even the earliest studies of fixation behavior noted considerable individual differences (19, 20), which recently gained wide-spread interest, ranging from behavioral genetics to computer science. Basic occulomotor traits, like mean saccadic amplitude and velocity, reliably vary between observers (2128). Gaze predictions based on artificial neural networks can improve when being trained on individual data (28, 29), or taking observer properties like age into account (30).…”
mentioning
confidence: 99%
“…A collective review of related work published prior to 2015 may be found in [18]. Moreover, comparative results for studies analyzing common datasets are provided in [19], which summarizes the results of the most recent BioEye competition. As noted within these reviews, the majority of prior work uses a common processing pipeline, with the recordings initially partitioned into specific eye movement events using a classification algorithm, followed by the formation of the biometric template as a vector of discrete features from each event.…”
Section: Prior Workmentioning
confidence: 99%